Is the nutritive value of tall fescue (Festuca arundinacea Schreb.) related to the accumulated forage mass? - Scheneiter, Jorge Omar; Camarasa, Jonatan Nicolás; Carrete, Jorge Ricardo; Amendola, C. (Wiley, 2019)
The aim of this work was to investigate whether neutral detergent fibre (NDF) and dry‐matter digestibility (DMD) are related to tall fescue accumulated forage mass (AFM) and to assess the relevance of environmental variables to predict the nutritive value of tall fescue swards. Three experiments were carried out in Pergamino, Argentina. To obtain swards with different amounts of AFM, two N levels and two irrigation regimes were applied in the spring after sowing and the autumn of the next year. In spring and autumn, AFM, NDF and DMD were measured every 10–12 days. In spring, NDF increased from 503 to 604 g kg−1, DMD decreased from 684 to 558 g kg−1 and AFM increased from 0·64 to 2·82 t DM ha−1. In autumn, NDF decreased from 543 to 442 g kg−1, DMD increased from 591 to 681 g kg−1 and AFM increased from 0·35 to 1·10 t DM ha−1. The results show that the nutritive value of tall fescue through the year is not related to the accumulation of dry matter of the sward. Nutritive value is determined by the reproductive stage in late spring and early summer, the fate of photosynthates at different times of the year and the synthesis of non‐digestible compounds.